1958
DOI: 10.2134/agronj1958.00021962005000090005x
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Milling Quality in Wheat as Measured by the Separation of the Bran and Endosperm1

Abstract: Synopsis Gene number affecting milling quality in a wheat cross (Norin 10 × Brevor‐14) × Burt could not be determined using the partitioning method of genetic analysis. The components of variance were partitioned and a heritability of 35.50% was determined for this character. Estimates of expected genetic gain indicated good progress could be made in a recurrent selection program for milling quality as measured by the separation of bran and endosperm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1964
1964
1977
1977

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Heritability estimates obtained in the present study revealed that the traits test weight, flour yield, grain protein, flour protein, colour grade and particle size index were highly heritable, while the traits baking score and baking volume were moderately heritable. The heritabilities are in close agreement with those reported by BAKER et al (1971), DAVIS et al (1961 and EVERSON & SEEBORG (1958). Heritabilities reported for most of the important quality traits, in general, suggest that the inheritance of quality characters may be more simple than was formerly supposed as also observed by HEVNE & S~ITrI (1967).…”
Section: Osupporting
confidence: 88%
“…Heritability estimates obtained in the present study revealed that the traits test weight, flour yield, grain protein, flour protein, colour grade and particle size index were highly heritable, while the traits baking score and baking volume were moderately heritable. The heritabilities are in close agreement with those reported by BAKER et al (1971), DAVIS et al (1961 and EVERSON & SEEBORG (1958). Heritabilities reported for most of the important quality traits, in general, suggest that the inheritance of quality characters may be more simple than was formerly supposed as also observed by HEVNE & S~ITrI (1967).…”
Section: Osupporting
confidence: 88%